Recent advances in remotely controlled pulsatile drug delivery systems - Al Zahraa Khalifa; Houralaeen Zyad; Hoor Mohammed; Kenda Ihsan; Leen Alrawi; Maryam Abdullah; Ola Akram (Wolters Kluwer Medknow Publications, 2022)
Pharmaceutical technology is drastically developing to enhance the efficacy and safety of drug therapy. Pulsatile delivery systems, in turn, gained attraction for their ability to deliver the right drug amount to the right body site, at the right time which is advantageous over conventional dosage forms. Their use is associated with increased patient compliance and allows on-demand drug delivery as well as customizable therapy. Recent technologies have been implemented to further develop pulsatile delivery systems for more precise determination of the dosage timing and duration as well as the location of drug release. Great interests are directed towards externally regulated pulsatile release systems which will be the focus of this review. The recent advances will be highlighted in remotely controlled delivery systems. This includes electro responsive, light-responsive, ultrasound responsive, and magnetically induced pulsatile systems as well as wirelessly controlled implantable systems. The current status of these technologies will be discussed as well as the recent investigations and future applications.